1999
DOI: 10.2514/2.663
|View full text |Cite
|
Sign up to set email alerts
|

Normal Vortex Interaction with a Circular Cylinder

Abstract: Interaction of a columnar vortex with a long circular cylinder translated normal to the vortex axis is examined for the case where the cylinder diameter is much larger than the vortex core radius. The study focuses on understanding and quantifying the limitations of traditional vortex lament models arising from vortex-induced separation of the cylinder boundary layer and vortex core shape deformation. These limitations are examined over a wide range of values of the impact parameter, de ned as the ratio of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(25 reference statements)
3
9
0
Order By: Relevance
“…6d). The tornado vortex behavior during the interaction with a wall reveals very similar characteristics as a normal vortex interaction with a thick cylinder (Krishnamoorthy et al 1999), in which laboratory experiments showed substantial streamwise bending and spanwise displacement of a vortex during the impact.…”
Section: Tornado Vortex Bending and Displacement During The Interactionmentioning
confidence: 79%
See 3 more Smart Citations
“…6d). The tornado vortex behavior during the interaction with a wall reveals very similar characteristics as a normal vortex interaction with a thick cylinder (Krishnamoorthy et al 1999), in which laboratory experiments showed substantial streamwise bending and spanwise displacement of a vortex during the impact.…”
Section: Tornado Vortex Bending and Displacement During The Interactionmentioning
confidence: 79%
“…In the orthogonal blade-vortex interaction and the cylinder-vortex interaction it was commonly observed that the translating vortex was influenced by the wall at some distance before the impact (Krishnamoorthy and Marshall 1998;Krishnamoorthy et al 1999). The cause was the boundary layer separation and ejection of secondary vortices from the body leading surface.…”
Section: Secondary Vorticity Ejection and Vortex Breakdownmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, it is observed from Figs. 2(d) and 2(e) that a series of loop-like vortices (Krishnamoorthy and Marshall 1998;Krishnamoorthy et al 1999;Gossler and Marshall 2001) and hair-pin vortices (Hon and Walker 1991;Adrian 2007;Liu and Chen 2011) wrapping around the vortex rings are formed. With the evolution of vortical structures, it is seen that the strength and number of the wrapping vortices are increased con-siderably as shown in Figs.…”
Section: Vortical Structuresmentioning
confidence: 99%